Efecto de tres fuentes y cuatro niveles de abono sobre el rendimiento de maíz (zea mays l.), variedad marginal 28 tropical en Valle del Bajo Mayo - Pretell Paredes, Carlos Enrique (2002)
With the objective of evaluating the effect of three sources and three levels of application of organic fertilizers on maize yield Marginal 28TropicaJ variety, as well as the respective economic analysis, was carried out this work, which was carried out in 9-A lot of station Experimental "El Porvenir", Juan Guerra, the low may Valley District , province and region San Martfn (Peru), geographically characterized by the following coordinates: latitude South 06 ' 36' 15 "and length West 76 ° 21' 15"; an altitude of 232 msnmm, and be located in a dry Tropical Forest (b-ST); and with the following features physical and chemical soil: clayey texture, pH 7.1, available phosphorus 29.7 rngfl, potassium 0.41 meq / 100g, 3.24% organic matter and contents Ca + Mg of 42.0 meq / 100g. Was used the statistical design of completely randomized blocks, with a factorial arrangement 3 • 4, split plot. Sources of organic fertilizer that were evaluated were: manure from cattle, sheep and earthworm Humus manure; While the levels of application were: 3, 6 and 9 TM / has. The results were analyzed by analysis of variance (ANOVA) and Duncan. Multiple testing, having weights they fluctuated from 4 636,11 Kg / has 6 458,33 kg / Ha, corresponding the lower yield T 1 (control) treatment and the highest yield to treatment T12 (9 TM / has of Vermicompost). When including economic analysis is that with increased grain yield treatments had higher production costs and therefore a negative return, hence the treatments that reached more yields do not constitute the most profitable.